Rola elastyczności w rewolucyjnym i ewolucyjnym rozwoju przedsiębiorstwa - Osbert-Pociecha, Grażyna (The significance of flexibility for both revolution and evolution development of organization, 2006)
In this article the revolution and evolution changes in organization were presented as the power of its development. Using some models author has showed the need to integrate them. The flexibility of organization was emphasized as ability to link a different kind of changes.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 133-138